You can die - Zanetti, Rebecca (Zanetti, Rebecca. Laurel Snow thriller, 2023)
FBI profiler Laurel Snow investigates bodies found with valentine candy hearts shoved down their throats. Then the case takes a shockingly personal turn when the father she's never met turns up among the dead.